A two step method for the preparation of carbamate cross-linked cellulose films using an ionic liquid and their water retention properties. (10th December 2016) - Amarasekara, Ananda S.; Hasan, Muhammad A.; Ha, Uyen
Highlights: Carbamate cross-linked cellulose films were prepared using an ionic liquid medium. New technique involves the cross-linking reaction in a pre-formed cellulose coating. Films were characterized by FT-IR, and TG-DTA. Water retention of films decreases with increase in hydrophobicity of the carbamate. Abstract: Carbamate cross-linked cellulose films can be prepared in a two step method using cellulose dissolved in 1- n -butyl-3-methylimidazolium chloride ionic liquid. The new technique involves casting the film from cellulose ionic liquid solution onto a glass surface and application of alkyl/aryl diisocyanate in dry dimethylsulfoxide solution onto the cellulose – ionic liquid coating on glass and allowing the cross-linking reaction to occur on the pre-formed cellulose coating. The carbamate cross-linked cellulose films formed were characterized by FT-IR, and TG-DTA. The water retention values of the films are shown to decrease with the increase in hydrophobicity of the alky/aryl group linker in the carbamate bridges.